Effectiveness Of Industrialised Building System (IBS) By Using Expanded Polystyrene (EPS) - A Case Study Of Project Finance Initiative 2 (PFI2) Student Hostels For 4000 Students At Pauh Putra Main Campus Universiti Malaysia Perlis (UniMAP) - Siti Nursyahira Khairil Anuar (School of Environmental Engineering, Universiti Malaysia Perlis, 2016)
The objectives of this study are listed below to identify the building structural elements of IBS by using EPS used in project of student hostel in Pauh Putra Main Campus UniMAP. To identify the process involved in the construction of the project by using EPS. To study the effectiveness of IBS using EPS panels for building structural elements involved, which are the cost estimation, rapid completion period, the use of minimal labor and perfect quality control.